Does parkland influence walking? The relationship between area of parkland and walking trips in Melbourne, Australia - King Tania L; Thornton Lukar E; Bentley Rebecca J; Kavanagh Anne M (BMC, 2012)
Abstract Background Using two different measures of park area, at three buffer distances, we sought to investigate the ways in which park area and proximity to parks, are related to the frequency of walking (for all purposes) in Australian adults. Little previous research has been conducted in this area, and results of existing research have been mixed. Methods Residents of 50 urban areas in metropolitan Melbourne, Australia completed a physical activity survey (n = 2305). Respondents reported how often they walked for ≥10 minutes in the previous month. Walking frequency was dichotomised to 'less than weekly' (less than 1/week) and 'at least weekly' (1/week or more). Using Geographic Information Systems, Euclidean buffers were created around each respondent's home at three distances: 400metres (m), 800 m and 1200 m. Total area of parkland in each person's buffer was calculated for the three buffers. Additionally, total area of 'larger parks', (park space ≥ park with Australian Rules Football oval (17,862 m2)), was calculated for each set of buffers. Area of park was categorised into tertiles for area of all parks, and area of larger parks (the lowest tertile was used as the reference category). Multilevel logistic regression, with individuals nested within areas, was used to estimate the effect of area of parkland on walking frequency. Results No statistically significant associations were found between walking frequency and park area (total and large parks) within 400 m of respondent's homes. For total park area within 800 m, the odds of walking at least weekly were lower for those in the mid (OR 0.65, 95% CI 0.46-0.91) and highest (OR 0.65, 95% CI 0.44-0.95) tertile of park area compared to those living in areas with the least amount of park area. Similar results were observed for total park area in the 1200 m buffers. When only larger parks were investigated, again more frequent walking was less likely when respondents had access to a greater amount of park area. Conclusions In this study we found that more park area in residential environments reduced the odds of walking more frequently. Other area characteristics such as street connectivity and destinations may underlie these associations by negatively correlating with park area.